VETERINARY-SANITARY EVALUATION OF RABBIT MEAT CONTAMINATED WITH CYPERMETHRIN - Nurullayev Alisher Abdullayevich; Docent Kholikov Abror Azamovich; Master Alisher Shomakhsudov (European Journal of Agricultural and Rural Education, 2022)
The quality of rabbit meat poisoning was analyzed and evaluated on the basis of veterinary-sanitary, bacteriological, organoleptic and biochemical tests